Building Degree Profiles. The Tuning Approach - Julia González; Maria Yarosh (Universidad de Deusto, 2014)
The development of degree profiles is an important art which has become quite specialized in recent years. This article concentrates on the analysis of the importance of the role of degree profiles in the design of degrees and, as a consequence, in Higher Education in general. It analyses, particularly, the work of the Tuning Project and its main processes in relation to profile building. It also gathers together and systematizes the specific contribution of four main components which should be taken into consideration at the time of the creation of new qualifications: two of the components relate to the analysis of social and professional needs and the future trends in the area. Both of these elements provide the relevance which a degree profile should strive to attain. The third component, the reference to the meta-profile, provides a capacity for recognition throughout an entire region and also in relation to the global context. The last element in profile development takes into consideration the university where the programme is anchored, its mission and strengths.